ANALISIS GAYA BAHASA DALAM NOVEL BILA ESOK IBU TIADA KARYA NUY NAGIGA - Lestari, Diyan; Irawan, Dody; Lolita, Asri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to describe the rhetorical style in the novel Bila Esok Ibu Tiada. The method used in this study is descriptive. The type of research is qualitative. The data collection technique is reading and note-taking. The data analysis techniques used are data reduction, data presentation, and conclusion. The instrument in this study used a rhetorical style analysis method based on the theory of Saryono, et al. The results of this study obtained 49 forms of rhetorical style as follows: Climax style, which states a word sequentially with increasing intensity, with 8 data points; anticlimax, which decreases in intensity, with 1 data point; and gradation, which consists of several ideas stated with sequential words. Words mentioned at the end of the first idea are repeated at the beginning of the second idea, words mentioned at the end of the second idea are repeated at the beginning of the third idea, and so on, with 6 data points; paradox, which contains a real contradiction with existing facts, with 1 data point; pleonasm, which uses more words than necessary, with 5 data points; tautology uses repetition of meaning as an explanation, there is 1 data, antithesis is a style of language that describes something using words with opposite meanings, there is 1 data, repetition or repetition of words, there are 5 data, anaphora is the repetition of words at the beginning of a sentence, there are 10 data, epiphora is the repetition of words at the end of sentences in 8 data points, assonance in the form of vowel repetition in 1 data point, and dissonance or combinations of unpleasant sounds in 2 data points.